Learning to do responsible innovation in industry: six lessons. Issue 3 (1st September 2020) - van de Poel, Ibo; Asveld, Lotte; Flipse, Steven; Klaassen, Pim; Kwee, Zenlin; Maia, Maria; Mantovani, Elvio; Nathan, Christopher; Porcari, Andrea; Yaghmaei, Emad
ABSTRACT: There is now almost a decade of experience with RRI (Responsible Research and Innovation), including a growing emphasis on RRI in industry. Based on our experiences in the EU-funded project PRISMA, we find that the companies we engaged could be motivated to do RRI, but often only after we first shifted initial assumptions and strategies. Accordingly, we formulate six lessons we learned in the expectation that they will be relevant both for RRI in industry as well as for the future of RRI more broadly. These lessons are: (1) Strategize for stakeholder engagement; (2) Broaden current assessments; (3) Place values center stage; (4) Experiment for responsiveness; (5) Monitor RRI progress; and (6) Aim for shared value.